If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying s = 4s + -6 Reorder the terms: s = -6 + 4s Solving s = -6 + 4s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-4s' to each side of the equation. s + -4s = -6 + 4s + -4s Combine like terms: s + -4s = -3s -3s = -6 + 4s + -4s Combine like terms: 4s + -4s = 0 -3s = -6 + 0 -3s = -6 Divide each side by '-3'. s = 2 Simplifying s = 2
| -0.9x+xy-0.8y+2y= | | 100x^2-4=0 | | 7=-56w | | c=38.34+0.50x | | 38.34=c+0.50x | | 3(y-2)=15-4y | | 74-3x=6x+23 | | 38.34=cx+0.50 | | C=24+35 | | 6+3n=4-5n | | 10+4q=12+3q | | 77-9y=23 | | x=38.34x+0.50 | | 15=-.6n | | 3x+5+3y+108=180 | | 4(x+5)=5(3x-7) | | 3*4-8=8 | | x+5=y-50 | | 8x-6=32 | | 3x+5+37+108=180 | | 15-x=5.2 | | 5b+40=20b+40 | | 8+m=9m-7 | | -z+6=-6 | | 5b+40=200b+400 | | 60-5x=22x+18 | | 2x=7y-11 | | 4x+4x=23x | | y/78+93=95 | | (7)-(14)= | | 3x+15+8=3x+15 | | 3f-8=f |